2018
DOI: 10.1097/rlu.0000000000002175
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 68Ga-PSMA-11 PET/CT in Imaging of Glioma—A Pilot Study

Abstract: In the evaluation of gliomas, Ga-PSMA-11 PET/CT brain imaging is a potentially useful imaging tool. The use of Ga-PSMA-11 brain PET/CT in evaluation of recurrent glioma seems promising. Absence of physiological uptake of Ga-PSMA-11 in the normal brain parenchyma results in high TBR values and consequently better visualization of glioma lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 32 publications
4
86
1
Order By: Relevance
“…This result confirms the higher tumour specificity of PSMA compared to FET and it suggests that, in patients with positive tumour uptake, 68 Ga-PSMA-617 has a greater clinical potential than 18 F-FET and 18 F-FDG as a tracer for the visualisation of recurrent tumour lesions and for secondary treatment planning. It is worth noting that this observation not only is in agreement with the observations reported in recent studies of recurrent GBM patients, 321,322,326 but also adds value to the literature of case studies reporting the value of 68 Ga-PSMA as a better PET tracer than FDG for the diagnosis, monitoring and treatment planning for primary GBM lesions. 319,331 The results obtained with the mirror-image method were validated by using a second method for the selection of the background activity reference in the contralateral normal brain.…”
Section: Feature Extractionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result confirms the higher tumour specificity of PSMA compared to FET and it suggests that, in patients with positive tumour uptake, 68 Ga-PSMA-617 has a greater clinical potential than 18 F-FET and 18 F-FDG as a tracer for the visualisation of recurrent tumour lesions and for secondary treatment planning. It is worth noting that this observation not only is in agreement with the observations reported in recent studies of recurrent GBM patients, 321,322,326 but also adds value to the literature of case studies reporting the value of 68 Ga-PSMA as a better PET tracer than FDG for the diagnosis, monitoring and treatment planning for primary GBM lesions. 319,331 The results obtained with the mirror-image method were validated by using a second method for the selection of the background activity reference in the contralateral normal brain.…”
Section: Feature Extractionsupporting
confidence: 90%
“…278,297,299,311 The mechanisms of immunemodulation induced by FUS-assisted BBB opening have been comprehensively reviewed by Chen et al 312 PSMA is a cell-surface protein that is highly expressed in prostate cancer 313 and also in the endothelium of the tumour neovasculature of several solid tumours, 314 including GBM, 315-318 making it an excellent target for antibody-drug conjugates or peptide receptor radionuclide therapy. 315 Recently 68 Ga-PSMA-11 has also been shown to be a promising PET imaging agent for the diagnosis of patients with primary GBM 319 and for assessing tumour recurrence, 321,322 and as such, it has a great potential for treatment stratification purposes. 319 Modifications of the PSMA-11 peptide have resulted in the development of the small-molecule ligand PSMA-617, which has the advantage of being suitable for radiolabelling with different radioisotopes, including 68 Ga, 177 Lu,111 In and 90 Y, and thus, it can be used for both PET diagnostic imaging and radionuclide targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSMA expression was found in endothelial cells associated with neovascularization and, for these reasons, can be a very interesting marker for monitoring anti-angiogenic drugs [314] At the moment, only few studies evaluating PSMA targeted imaging of gliomas/glioblastomas in clinical practice are currently available. Moreover, most of these studies are case reports or case series [255][256][257][258][259][260][261][262][263][264]315]. Although limited, these studies confirmed that high-grade glioma/glioblastoma are PSMA-avid compared to low-grade and PSMA radioligand mainly binds vascular endothelial cells.…”
Section: Other Targets Of Tumour Microenvironmentmentioning
confidence: 84%
“…76 Various PET agents targeting prostate specific membrane antigen have been shown to bind to tumor blood vessels, including those in glioma, and at least one of these agents is likely to gain FDA approval in the foreseeable future. 77 A wide variety of other PET agents have been described, allowing imaging of DNA replication, neoangiogenesis, and hypoxia, amongst other targets. 74 Figure 10.…”
Section: Positron Emission Tomographymentioning
confidence: 99%